KETERLIBATAN MASYARAKAT PEMILIK TANAH PADA PROGRAM REDISTRIBUSI TANAH DALAM MEWUJUDKAN KETAHANAN PANGAN DI ERA NEW NORMAL - Zuhrotul Atsna; Lintar Brillian Pintakami; Eko Wahyu Budiman (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2022)
This study was carried out with the aim of describing the involvement of the landowner community in the land redistribution program in the new normal era, and analyzing the outpouring of community work in land redistribution management in the new normal era, as well as the contribution of the landowner community in the land redistribution program in realizing food security in the new normal era. The qualitative research method is a case study form. Data was collected through interviews, observation and sampling with the snowball sampling method obtained by 16 informants and 4 key informants purposively. The results showed that community involvement in the land redistribution program was considered positive and quite active with a score of 85%-75%. The workload of the community in the new normal era shows that there is no significant change in work activities, only a 2 hour difference in working time. The contribution of land owners to food security is considered adequate, which means that food needs are fulfilled in the new normal.